Clinical efficacy of plasmid encoding p62/SQSTM1 (Elenagen) in combination with gemcitabine in patients with platinum-resistant ovarian cancer: a randomized controlled trial - Krasny, Sergei; Baranau, Yauheni; Polyakov, Sergey; Zharkova, Ekaterina; Streltsova, Olga; Filimonava, Aliona; Siarheyeva, Volha; Kazlouskaya, Sviatlana; Khorau, Anton; Gabai, Vladimir; Shneider, Alexander (Frontiers in Oncology, 2024)
The purpose of this trial is to evaluate the safety and efficacy of ELENAGEN, a novel anticancer therapeutic DNA plasmid encoding p62/SQSTM1 protein, as an adjuvant to chemotherapy with gemcitabine (GEM) in patients with advanced platinum-resistant ovarian cancer.Methods: This open-label prospective randomized study with two arms. GEM (1000 mg/m 2 ) on days 1 and 8 every 3 weeks was administered in both arms: in the Chemo arm (n = 20), GEM was the only treatment, and in the ELENAGEN arm (n = 20), GEM was supplemented with ELENAGEN (2.5 mg i.m. weekly). The primary endpoint was progression-free survival (PFS), and the secondary endpoint was safety. Antitumor activity was assessed by RECIST 1.1, and criteria safety was assessed according to NCI CTCAE version 5.0.According to the cutoff data, the median follow-up was 13.8 months. There were no serious adverse events related to ELENAGEN treatment. The median PFS was 2.8 and 7.2 months in the Chemo and ELENAGEN arms, respectively (p Log-Rank = 0.03). Notably, at the time of cutoff, 9 patients (45%) in the ELENAGEN arm did not progress, with the longest PFS recorded thus far being 24 months. Subgroup analysis of patients in both arms demonstrated high efficacy of ELENAGEN in patients with worse prognostic factors: high pretreatment levels of CA125 and progression after platinum-free interval <3 months.The addition of ELENAGEN to gemcitabine is effective in patients with platinumresistant ovarian cancer, including those with a worse prognosis.